Neuromodulation of safety and surprise in the early stages of infant development: affective homeostatic regulation in bodily and mental functions - Clarici, Andrea; Bulfon, Matteo; Radin, Yvonne; Panksepp, Jaak (Frontiers in Psychology, 2024)
Developing a sense of internal safety and security depends mainly on others: numerous neuromodulators play a significant role in the homeostatic process, regulating the importance of proximity to a caregiver and experiencing feelings that enable us to regulate our interdependence with our conspecifics since birth. Panksepp (1998) named this array of neurofunctional structures the SEPARATION DISTRESS system (now more commonly known as the PANIC/GRIEF system). This emotional system is mainly involved in the insurgenceproduction of depressive symptoms. The disruption of this essential emotional balance leads to the onset of feelings of panic followed by depression. We will focus on the neuropeptides that play a crucial role in social approach behaviour in mammals, which enhance prosocial behaviour and facilitate the consolidation of social bonds. We propose that most prosocial behaviours are regulated through the specific neuromodulators acting on the precision of salient intersubjective stimuli, reflecting an increased sense of inner confidence (safety) in social relationships. This review considers the neurofunctional link between the feelings that may ultimately be at the base of a sense of inner safety and the central neuromodulatory systems. This link may shed light on the clinical implications for the development of early mother-infant bonding and the depressive clinical consequences when this bond is disrupted, such as in post-partum depression, depressive feelings connected to endometriosis, addiction, neurofunctional disorders, and psychological trauma.